Feline cranial cruciate rupture - Harasen, G. L. G. (Veterinary and Comparative Orthopaedics and Traumatology, 2005)
Seventeen cases of feline cranial cruciate ligament rupture are presented. The cases are divided into two groups: those with traumatic multiligamentous damage, and those with isolated cranial cruciate ligament rupture without a history of trauma. The cats that had suffered cruciate ligament rupture were heavier than the general population of cats and there is evidence reported that this injury parallels the degenerative cranial cruciate ruptures seen in overweight small breed dogs. The limited literature on this subject is reviewed including approaches to treatment.
Keywords: Feline; cranial cruciate ligament